Present images: public space intervention in commemoration of the 40 years of the civil-military coup of 1976 (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In this paper we want to point out the importance of images in memory building processes. The image as a way to represent and invoke the past, constitutes a key starting point to address its uses and political potentialities in relation to violence and demands for truth and justice. We focus on examples of photographic production linked to the construction of memory on State Terrorism in Argentina. We address how the photographic production of a particular period acquires new meanings and uses from new appropriations in different historical contexts. In particular, we develop how the production of a personal photographic archive emerges in the public space in another political context, acquiring different nuances of collective political action.In this analysis, we discuss the intervention in public space proposed by Asociación de Reporteros Gráficos de la República Ar- gentina (A.R.G.R.A.) for the 40th anniversary’s commemoration of the 1976 military coup.
Keywords: Photography; Memory, Public Space; Collective Action.